Epidemiological African day for evaluation of patients at risk of venous thrombosis in acute hospital care settings - Kingue, Samuel (Clinics Cardive Publishing, 2014)
INTRODUCTION: This study aimed to identify patients at risk for venous thromboembolism (VTE) among all patients hospitalised, and to determine the proportion of at-risk hospital patients who received effective types of VTE prophylaxis in sub-Saharan Africa (SSA). METHODS: A multinational, observational, cross-sectional survey was carried out on 1 583 at-risk patients throughout five SSA countries. RESULTS: The prevalence of VTE risk was 50.4% overall, 62.3% in medical and 43.8% in surgical patients. The proportion of at-risk patients receiving prophylaxis was 51.5% overall, 36.2% in medical and 64% in surgical patients. Low-molecular weight heparin was the most frequently used prophylactic method in 40.2% overall, 23.1% in medical and 49.9% in surgical patients. DISCUSSION: This study showed a high prevalence of VTE risk among hospitalised patients and that less than half of all at-risk patients received an American College of Clinical Pharmacy-recommended method of prophylaxis. CONCLUSION: Recommended VTE prophylaxis is underused in SSA.